Drug Resistance in Cortical and Hippocampal Slices from Resected Tissue of Epilepsy Patients: No Significant Impact of P-Glycoprotein and Multidrug Resistance-Associated Proteins - Sandow, Nora; Kim, Simon; Raue, Claudia; Päsler, Dennis; Klaft, Zin-Juan; Antonio, Leandro Leite; Hollnagel, Jan Oliver; Kovacs, Richard; Kann, Oliver; Horn, Peter; Vajkoczy, Peter; Holtkamp, Martin; et al. (Frontiers in Neurology, 2015)
Drug resistant patients undergoing epilepsy surgery have a good chance to become sensitive to anticonvulsant medication, suggesting that the resected brain tissue is responsible for drug resistance. Here, we address the question whether P-glycoprotein (Pgp) and multidrug resistance associated proteins (MRPs) expressed in the resected tissue contribute to drug resistance in vitro. Effects of anti-epileptic drugs (carbamazepine, sodium valproate, phenytoin) and two unspecific inhibitors of Pgp and MRPs (verapamil and probenecid) on seizure-like events induced in slices from 35 hippocampal and 35 temporal cortex specimens of altogether 51 patients (161 slices) were studied. Although in slice preparations the blood brain barrier is not functional, we found that seizure-like events predominantly persisted in the presence of anticonvulsant drugs (90%) and also in the presence of verapamil and probenecid (86%). Following subsequent co-administration of antiepileptic drugs and drug transport inhibitors, seizure-like events continued in 63% of 143 slices. Drug sensitivity in slices was recognized either as transition to recurrent epileptiform transients (30%) or as suppression (7%), particularly by perfusion with carbamazepine in probenecid containing solutions (43%, 9%). Summarizing responses to co-administration from more than one slice per patient revealed that suppression of seizure-like activity in all slices was only observed in 7 % of patients. Patients whose tissue was completely or partially sensitive (65 %) presented with higher seizure frequencies than those with resistant tissue (35 %). However, corresponding subgroups of patients don’t differ with respect to expression rates of drug transporters. Our results imply that parenchymal MRPs and Pgp are not responsible for drug resistance in resected tissue.